Effectiveness of Health Education Using E-Booklet Media in Increasing Contraceptive Knowledge in Fertile Age Couples (HEALTH CARE: JURNAL KESEHATAN, 2025)
Contraceptive information is very important in supporting the success of family planning programs. Therefore, health education to provide health information in an effort to increase knowledge is very necessary. In order to facilitate the delivery of information, tools or media are needed. One of the information media that can be used is e-booklet media, which contains visual elements in the form of text and images, which are interactive and easy to access. This study aims to determine the effectiveness of e-booklet media as a contraceptive education tool for increasing knowledge in fertile couples (PUS). The research method uses a quantitative method using Quasi-experiment with a two-group pretest-posttest design. The study was conducted in the work area of ​​the Senapelan Health Center, Pekanbaru City. The population in this study were all fertile couples totaling 4,584. with a research sample of 44 fertile couples selected by purposive sampling which were divided into 2 groups, namely the intervention group (e-booklet media) and the control group (ABPK-KB media). Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data on knowledge of fertile couples about contraception were collected before and after counseling using e-booklet and ABPK-KB media. The analysis was conducted using a T-test to see the difference in the level of knowledge before and after health education was given using e-booklet media compared to using ABPK-KB media. The results of the T-test showed that there was a statistically significant increase in knowledge where e-booklet media was more effective in increasing knowledge about contraception in fertile couples compared to ABPK-KB media..